ANALYSIS OF THE DETERMINANTS OF EMPLOYEE PERFORMANCE - Siswadi, Yudi; Hsb, Jasman Saripuddin; Gusmiarni, Tri (International Proceeding of Law and Economic; 2020: International Proceeding of Law and Economic, 2021)
This study aims to determine and analyze whether organizational culture and discipline simultaneously (simultaneously) or partially have a significant effect on employee performance at PT. Bank Mandiri (Persero) Tbk Medan Area Imam Bonjol. This research uses an associative and quantitative approach. The population in this study were employees of PT. Bank Mandiri (Persero) Tbk Medan Area Imam Bonjol. The sample in this study used a saturated sample by taking all sections of the population of 88 employees. Data using multiple linear regression analysis methods, t test, f test and coefficient of determination using SPSS software version 20.0. based on research it can be concluded that (1) partially organizational culture on employee performance has positive and significant effect, (2) partially discipline on employee performance has positive and significant effect, (3) simultaneously organizational culture and discipline has positive and significant effect on employee performance at PT. Bank Mandiri (Persero) Tbk Medan Area Imam Bonjol.